(untitled) (Bulletin of Innovative Research, 2026)
This article examines the need for a comprehensive approach to the psychological training of 13- to 15-year-old boxers and their continuous improvement. Research has shown that meditation, visualization, and autogenic training are the most effective methods for overcoming competitive anxiety in young boxers. Psychological rehabilitation also plays an important role in the preparation of young boxers. The process of psychological recovery after a loss is crucial for boxers. Accepting defeat as a professional experience and drawing appropriate conclusions from it demonstrates an athlete’s psychological maturity. The role of the coach and team in psychological preparation is also important. They provide athletes with the necessary emotional support and strengthen their self-confidence. The article provides recommendations for sports coaches aimed at achieving effective results in overcoming competitive anxiety.